2015
DOI: 10.1007/s11606-015-3411-6
|View full text |Cite
|
Sign up to set email alerts
|

Future Research Prioritization: Implantable Cardioverter-Defibrillator Therapy in Older Patients

Abstract: BACKGROUND: Although the implantable cardioverterdefibrillator (ICD) is highly effective therapy for preventing sudden cardiac death, there is considerable uncertainty about its benefits and harms in older patients, especially in the presence of factors, other than old age, that increase the risk of death. OBJECTIVE: To develop a prioritized research agenda for the Patient-Centered Outcomes Research Institute as informed by a diverse group of stakeholders on the use and outcomes of the ICD in older patients. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…20,26 This uncertainty is amplified in patients ≥65 years of age in whom the burden of comorbid diseases and competing modes of death reduce ICD benefit. 26,27 Although many studies have defined the risks associated with ICD generator replacement, 28,29 there are currently no studies that have examined whether or not this invasive procedure leads to any benefit among these lower-risk patients.…”
Section: Data On Icdsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,26 This uncertainty is amplified in patients ≥65 years of age in whom the burden of comorbid diseases and competing modes of death reduce ICD benefit. 26,27 Although many studies have defined the risks associated with ICD generator replacement, 28,29 there are currently no studies that have examined whether or not this invasive procedure leads to any benefit among these lower-risk patients.…”
Section: Data On Icdsmentioning
confidence: 99%
“…The results identified “clinical effectiveness and safety of ICD replacements in older patients who have not had an appropriate shock or those with improved LVEF” as a key research priority for PCORI. 26 …”
Section: Data On Icdsmentioning
confidence: 99%
“…There are limited data on the prognostic implications of LVEF change over time, particularly as it pertains to the risk for ventricular arrhythmias, and there are currently no guidelines to aid in clinical decision making. (7,8) Based on this important evidence gap, we performed an analysis assessing the clinical utility of long-term follow-up LVEF in a primary prevention ICD population to determine the relative clinical value of baseline and follow-up LVEF in estimating the risk for the following adverse clinical outcomes: left ventricular assist device implantation (LVAD), transplant, death, and ICD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4 Through the engagement of 18 stakeholders representing different perspectives and a forced-ranking prioritization method, they identified 12 areas of evidence gaps, which included the safety and effectiveness of ICDs in the elderly, the outcomes associated with different ICD devices, different modes of death or predictors of SCD in the elderly, the impact of ICDs on the quality of life, patient preferences regarding ICD implantation, and the shared decision-making process. 4 In order to reduce the waste of resources, it is crucial to clearly identify and prioritize research needs 5 using qualitative and quantitative research methods to cover both the depth and breadth of these gaps. The research priorities identified by AlKhatib and colleagues 4 could contribute to reducing some of the concerns in SCD prevention, but also to creating focused funding opportunities.…”
mentioning
confidence: 99%
“…4 In order to reduce the waste of resources, it is crucial to clearly identify and prioritize research needs 5 using qualitative and quantitative research methods to cover both the depth and breadth of these gaps. The research priorities identified by AlKhatib and colleagues 4 could contribute to reducing some of the concerns in SCD prevention, but also to creating focused funding opportunities.…”
mentioning
confidence: 99%